A Nearly Normal Family - Edvardsson, M. T.; Willson-Broyles, Rachel; Armitage, Richard, 1971-; Maguire, Georgia; Watson, Emily, 1967- (New York, New York : Macmillan Audio, 2019)
A legal thriller told in three acts follows the trial of an eighteen-year-old girl from an upstanding family who has been implicated in the murder of a shady businessman, testing the limits of her fathers faith and her mothers ethics.
Keywords: Families; Fiction; Trials (Murder); Fiction; Families; Fiction; Legal stories; Suspense fiction; Audiobooks